Temperature-dependent performance and constitutive modeling of additively manufactured Ti600 alloy - Tianhua Wen; Rui Fu; Sihang Xiao; Lei Zhang; Bo Song; Hongshuai Lei (Journal of Materials Research and Technology)
Titanium alloys produced through selective laser melting (SLM) are increasingly utilized in aerospace, defense, and marine sectors due to their design flexibility and high-temperature capabilities. Therefore, precise temperature-dependent characterization is essential for optimizing their engineering applications. This study investigates the thermal and mechanical properties of SLM-fabricated Ti600 alloy across a temperature range from room temperature to 700 °C. The findings indicate that thermal conductivity and thermal expansion both increased with temperature. Tensile testing shows a decrease in elastic modulus and ultimate tensile strength as temperature rises, with a significant decline observed near 550 °C. Microstructural analysis of tensile fractures reveals coarsening of the precipitated phase at temperatures above 500 °C, which correlates with the observed reduction in mechanical performance. Differential scanning calorimetry identifies 550 °C as a critical phase transition temperature, further explaining the degradation in properties. In addition, a temperature-dependent thermal performance prediction model and a bilinear temperature-dependent (BTD) constitutive model, incorporating strain hardening and phase transformation, were developed. Compared to the conventional Johnson-Cook constitutive model, the BTD model demonstrates superior accuracy in predicting stress-strain behavior at elevated temperatures. This study addresses the gap in knowledge regarding the high-temperature thermal and mechanical behavior of SLM-fabricated Ti600, offering valuable insights for its broader industrial application.